Future projections of total hip and knee arthroplasty in the UK: results from the UK Clinical Practice Research Datalink. Issue 4 (April 2015) - Culliford, D.; Maskell, J.; Judge, A.; Cooper, C.; Prieto-Alhambra, D.; Arden, N.K.; ,
Summary: Objective: To estimate the future rate of primary total hip (THR) or knee (TKR) replacement in the UK to 2035 allowing for changes in population demographics and obesity. Design: Using age/gender/body mass index (BMI)-specific incidence rates from a population-based cohort study of 50, 000 THR and 45, 609 TKR patients from the UK Clinical Practice Research Datalink (CPRD) between 1991 and 2010, we projected future numbers of THR and TKR using two models: a static, estimated rate from 2010 applied to population growth forecasts to 2035, and a log-linear rate extrapolation over the same period. Both scenarios used population forecast data from the UK Office for National Statistics (ONS). Results: Assuming rates of THR and TKR for 2010, and given projected population changes in age, gender and BMI, the number of THRs and TKRs performed in the UK in 2035 is estimated to be, respectively: 95, 877 and 118, 666. By comparison, an exponential extrapolation of historical rates using a log-linear model produces much higher estimates of THR and TKR counts in 2035 at 439, 097 and 1, 219, 362 respectively. Projected counts were higher for women than men. Assuming a changing (rather than fixed) future BMI distribution increases TKRs by 2035 but not THRs. Conclusions: Using historical rates and population forecasts we have projected the number of THR/TKR operations in the UK up to 2035. This study will inform policymakers requiring estimates of future demand for surgery. Incorporating future forecasts for BMI into projections of joint replacement may be more relevant for TKR rather than THR.